Thermal Performance Enhancement of Solar Water Heaters Using Phase Change Materials in Flat Plate Collectors - Saputra Sidabutar, Baginda; A. Abdullah, Nasruddin; Abdul Rahman, Nazaruddin; Amir, Fazri (Fakultas Teknik Universitas Samudra, 2024)
Solar water heaters are widely utilized for domestic hot water production, leveraging solar energy as a renewable and sustainable resource. However, the intermittent nature of solar radiation limits their efficiency, particularly during periods of low solar intensity or at night. This study investigates the thermal performance enhancement of solar water heaters through the integration of phase change materials (PCMs), specifically paraffin, within flat plate collectors. The paraffin PCM is placed within an additional pipe in the collector to store excess thermal energy during peak sunlight hours and release it when solar radiation is insufficient. Experimental tests were conducted to measure temperature fluctuations, heat storage capacity, and overall system efficiency with and without PCM integration. The results indicate that the addition of paraffin PCM significantly improves the system’s ability to retain heat, maintaining water temperatures above 50 °C for extended periods and increasing the overall efficiency of the solar water heater by 17.10%. This study demonstrates the potential of PCM-enhanced solar water heaters in optimizing energy use and improving thermal efficiency, making them more effective in regions with variable solar exposure.